The new EU counter-terrorism Agenda: preemptive security through the anticipation of terrorist events. Issue 5 (20th October 2021) - Baker-Beall, Christopher; Mott, Gareth
ABSTRACT: This article argues that the new EU Counter-Terrorism Agenda is based on logics of anticipatory action. Three types of anticipatory action that are central to the development of EU counter-terrorism are identified: preparedness, precaution and preemption. We argue that while the original EU Counter-Terrorism Strategy contained a mixture of these three forms of anticipatory action, the new Counter-Terrorism Agenda places a renewed emphasis on preemptive measures with preparedness given less prominence. The reinforcing of preemptive security practice is most vividly reflected in the CT Agenda's new Anticipate workstream, which emphasises the utility of preemptive computer-based technologies, including Artificial Intelligence and algorithms, as key dimensions of the response to terrorism. The article identifies challenges of transparency and effectiveness that arise when applying computer-based technologies to counter-terrorism, highlighting the importance of regulatory oversight if the EU's commitment to the development of security policies that respect fundamental rights is to be guaranteed.